Farming practices and productivity - Hailu, Getu; Weersink, Alfons; Minten, Bart (International Food Policy Research Institute, 2018)
In this chapter, teff production practices are described, along with their relationships with the level of land productivity of teff producers in Ethiopia. Data are used on plots of teff from a survey of 1,200 stratified randomly selected households conducted at the end of 2012. We selected this dataset as it provides high-quality data, relevant information on teff practices, and a large sample. The relationships between farming practices and teff yield are assessed through a descriptive analysis of the data and the estimation of a production function to determine teff productivity. Although input levels and characteristics of the plot and household are included as right-hand variables, the focus is on the technology employed and producer organizations used. The analysis sheds light on the relationships between farming practices and yield across plots as well as the implications for policies to improve land productivity for teff producers.